1970
DOI: 10.1088/0034-4885/33/2/301
|View full text |Cite
|
Sign up to set email alerts
|

Quantization of general relativity

Abstract: Contents 1. Introduction . 2. Motives , 2.1. Unacceptable difficulties in unquantized general relativity . 2.2. T h e basic tenets of contemporary physics demand that the gravitational field be quantized . 2.3. Quantum general relativity raises questions of measurement and interpretation which may contribute to an improved understanding of quantum theory . 2.4. Quantum general relativity promises rich rewards. 3.1, Geometrical background . 3.2. Action principle, field equations and Bianchi identities . 3.3. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Efforts to quantize Einstein gravity go back to the 1930s [58]; the field has repeatedly been reviewed [35,[59][60][61][62][63][64]. By 'conventional' quantum gravity we will mean here a theory that starts from a generating functional…”
Section: Quantizing Gravitymentioning
confidence: 99%
“…Efforts to quantize Einstein gravity go back to the 1930s [58]; the field has repeatedly been reviewed [35,[59][60][61][62][63][64]. By 'conventional' quantum gravity we will mean here a theory that starts from a generating functional…”
Section: Quantizing Gravitymentioning
confidence: 99%
“…According to Wheeler observable properties of matter and fields must be explained by geometrical and topological properties of space-time and the dynamics of matter and fields configuration are the result of the dynamics of space-time geometry and topology. This assumption and its motivations were discussed by many authors [2]- [17]. It was shown that the properties of matter and fields is indeed closely connected with the topology of space-time [18]- [20].…”
Section: Introductionmentioning
confidence: 99%
“…All existing attempts to describe topology change or topological fluctuation are phenomenological. It is often supposed that topology changes are pure quantum phenomena [2], [10], [9], [13], but there is no real progress in their quantum description also.…”
Section: Introductionmentioning
confidence: 99%
“…All attempts at the quantisation of general relativity have met so far with considerable difficulties (see Anderson 1964, Brill and Gowdy 1970, Ashtekar and Geach 1974. The problems are of various types, from the conceptual to the technical ones.…”
Section: Introductionmentioning
confidence: 99%